Original paperSense of coherence and strategies of coping with stress among patients suffering from rosacea and depression – a comparative study - Zboralski, Krzysztof; Gernand, Alicja; Orzechowska, Agata; Talarowska, Monika (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
The authors examined the dependency between the level of sense of coherence and the strategies of coping with stress in a group of patients suffering from psychiatric and dermatological disease. The examined group (n = 197) contained 69 patients suffering from depression and 98 patients diagnosed with rosacea. In the examinations Antonovsky’s Sense of Coherence Scale and the Moos Coping Test were used. Dermatological patients have a higher level of sense of coherence than psychiatric patients. In the case of the Moos Coping Test statistically significant differences were obtained in two scales: seeking information and support and taking problem-solving action. These mean values were higher also among patients suffering from rosacea.